Group Cognitive-Behavior Therapy or Group Metacognitive Therapy for Obsessive-Compulsive Disorder? Benchmarking and Comparative Effectiveness in a Routine Clinical Service - Papageorgiou, Costas; Carlile, Karen; Thorgaard, Sue; Waring, Howard; Haslam, Justin; Horne, Louise; Wells, Adrian (Frontiers in Psychology, 2018)
Cognitive-Behaviour Therapy (CBT), delivered in an individual or group format, is the recommended treatment of choice for Obsessive-Compulsive Disorder (OCD), but no studies have benchmarked the outcomes for group CBT in real-world clinical settings. The first aim of this evaluation was to benchmark the outcomes for group CBT in a sample of 125 patients who attended a routine clinical service for OCD. The results showed that the outcomes for the group CBT were comparable to those reported in previous treatment studies. However, consistent with the CBT for OCD literature, 28% of patients receiving CBT reported minimal improvement. The second aim of this evaluation was to carry out a benchmarking analysis for group Metacognitive Therapy (MCT) to determine if this could provide any advantages in a sample of 95 patients who also attended this clinical service over a subsequent period. The clinically significant results obtained for group MCT improved upon or equaled those obtained for group CBT and those typically found in treatment studies. The group MCT cohort improved significantly more than the group CBT cohort even after controlling for important pre-treatment variables including age, gender, number of diagnoses, symptoms of depression, and psychotropic medication. MCT had significantly higher clinical response rates. Based on international expert consensus criteria, 86.3% of patients in the MCT cohort responded compared with 64% in CBT. The implications of these findings are discussed.